Action‐project method: An approach to describing and studying goal‐oriented joint actions. Issue 2 (27th September 2022) - Shankar, Sneha; Young, Richard A.; Young, Meredith E.
Abstract: Context: Practicing health professionals and educators frequently act together in an interdependent or joint capacity to reach goals. Teaching or learning a new skill or engaging with patients in shared decision‐making exemplifies this joint and goal‐directed nature of Health Professions Education (HPE) and practice. However, building a robust understanding of the complexity of action, and joint action in particular, in HPE or patient care remains a challenge because of a limited number of methodologies available within HPE research. Methods: In this manuscript, we describe the Action‐Project Method (A‐PM) as a qualitative research approach that can be used to describe and understand goal‐directed joint actions. A‐PM is grounded in contextual action theory and is a methodology focussed on action as an object of study, as it is occurring. A‐PM uses three distinct perspectives to understand goal‐directed joint actions: observable behaviour, internal processes (i.e. reported thoughts and feelings) and the social meaning reflected in goals. Data collection in A‐PM involves observations, interviews, recording of actions and a self‐confrontation procedure—where participants watch video‐recorded segments of action and reflect on their internal processes, describing what they were thinking or feeling as they were completing the action. Together, the rich data generated and the layered approach to analysis provide a means to better understand the joint actions embedded in complex systems and collaborative work. Furthermore, the participants are treated as equal partners within A‐PM, ensuring data equity even when the research context includes hierarchical relationships. Discussion: Given increasing recognition to the importance of teamwork, relationships, interdependence, complex environments and centring patient or learner voices, A‐PM is a valuable research approach for HPE. A‐PM deepens our research arsenal with an approach that focusses on interdependent dyads or teams and provides a deeper understanding for how individuals engage together in goal‐oriented actions. Abstract : In this Research Approaches article, the authors critically outline the Action‐Project Method as a means of gaining deeper understanding into how individuals engage together in goal‐oriented actions.